Efectos de la población económicamente activa ocupada con educación superior y del comercio sobre el gasto real per cápita de los hogares en Loreto 2010-2021 - Guevara Trujillo, Gretty (2024)
Human capital theory suggests that higher educational levels are linked to higher income and productivity, both at the microeconomic level and in the economy as a whole. This research focuses on examining the association between the educational level, productivity and per capita spending of households in the Loreto region during the period 2010-2021. To achieve these objectives, a type of quantitative research has been used with a causal level and non-experimental design that uses longitudinal data. After identifying the optimal econometric model that includes 43 quarterly observations of the population under study and applies the OLS method for time series, it has been determined that an increase of 0.1% in the percentage of the economically active population employed with higher education generates an increase of S/ 58.60 in the real per capita spending of households in Loreto. Furthermore, it has been found that a 1% increase in the value produced by the economic activities of commerce results in an increase of S/ 1.62 in the real per capita expenditure of households in Loreto. These findings highlight the importance of higher education and the growth of commerce in improving the living conditions of the population.